Pembelajaran Keterampilan Cabang Olahraga Hoki melalui Pendekatan Model Peer Teaching - Hermawan, Irwan; Permadi, Asep Angga (Universitas Hamzanwadi, 2022)
This study aims to examine the learning of hockey skills through a peer teaching model approach. The method used in this study is an experimental method with The Static Pretest-Posttest Design. This study used a sample of 30 students. Based on the results of the analysis conducted by the researcher on the object under study, there is a significant effect of the peer teaching model on improving the learning outcomes of hockey skills. In this study, it is also known that the peer teaching model has a significantly more effective than the conventional model on improving hockey skills learning outcomes. This is because in peer teaching model students learn actively, thereby increasing their learning motivation. With higher learning motivation, students have a strong desire to master the skills taught by their own friends, this makes the learning process more effective so that it has a positive effect on improving learning outcomes. Thus, to improve student learning outcomes in learning hockey skills, peer teaching models can be used which provide high motivation and better influence on improving learning outcomes when compared to conventional learning models.